Fundamental of Entrepreneurship (ENT300) Assignment 3 : Business plan ancient golden bakery “CINNAMON” / Muhammad Haziq Rosli … [et al.] - Rosli, Muhammad Haziq; Raslan, Ras Alinie; Mohd Zahid, Nur Arnie Aryantie; Halid, Hasnida Harisya (2021)
The fundamentals of Entrepreneurship course (ENT300) have provided an assignment for students to dive deeper in the world of business and economy. The third assignment of our semester was finished by a team of five people working together to complete the project which was to create a business plan which related to our syllabus. Ancient Golden Bakery is a form of business based on partnership which consists of four members which hold important positions such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM 100,000.00 where the contribution of each member is RM 25,000. It is located at Ampang Malaysia. Ancient Golden Bakery is a company which focuses on production in Malaysia. This company provided food and drink which is wanted by the customer nowadays as it is easy to consume and has varieties. The Difference in recipe compared to our company recipe makes this food look more interesting and suitable with all types of food and drink especially for those who love to eat bread and cake. To make it more attractive we decided to make some innovation by implying our Ancient Golden Bakery’s own recipe.